2014
DOI: 10.4172/2161-1149.s4-002
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Interleukin-6 for the Treatment of Rheumatoid Arthritis: A Review and Update

Abstract: Tanaka et al., Rheumatol Curr Res 2013, S4 http://dx.doi.org/10.4172/2161-1149 Review ArticleOpen Access AbstractRheumatoid Arthritis (RA) is a chronic inflammatory disease, characterized by persistent joint inflammation, systemic inflammation and immunological abnormalities. Since IL-6 plays a major role in the development of these characteristics, its targeting could reasonably be expected to constitute a novel therapeutic strategy for the treatment of RA. Tocilizumab, a humanized anti-human IL-6 receptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 142 publications
(195 reference statements)
0
1
0
Order By: Relevance
“…However, the fact that both of these can be reduced by a single agent - Lex 2.6—is another encouraging factor suggesting efficacy of this peptide in the human disease, since it has been shown that interfering with the activity of either one of these cytokines alone has an effect on the disease, in the case of IL6, reducing the destructive effects on synovial fibroblasts. [18,19,20]. The results of experiments to identify the receptor responsible for down-regulation of secretion of these cytokines will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…However, the fact that both of these can be reduced by a single agent - Lex 2.6—is another encouraging factor suggesting efficacy of this peptide in the human disease, since it has been shown that interfering with the activity of either one of these cytokines alone has an effect on the disease, in the case of IL6, reducing the destructive effects on synovial fibroblasts. [18,19,20]. The results of experiments to identify the receptor responsible for down-regulation of secretion of these cytokines will be reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%